Organización y semántica naval moderna - Blanco Núñez, José María (Cuadernos de Historia Moderna, 2006)
This article looks at the use of seafaring language in the Modern Era. It dwells especially on the words “escuadra”, “flota” and “convoy” (squadron, fleet and convoy), examining the mutations therein during the imperial wars waged between Charles V (Charles I of Spain) and Francis I of France, which favoured the birth and development of Atlantic piracy. It analyses the names of the various functional navies, created on an ad hoc basis as the various weak points appeared in Spain’s traffic with the Americas. The article also deals with the commanders of these groups and the names given to the onboard personnel. Specific examples are given of modern semantics with comments on the changes that occurred upon the advent of the Bourbons and the creation of the Military Navy of Spain (Marina Militar de España). The paper also investigates the rich semantics of the rudimentary naval artillery of the time and then winds up with a section on naval architecture, a field so vast it would really need an article in its own right.